Kinetics Study, and Proposed Mechanism for the Photochemical Reduction of Chromium (VI) by Iron(III)-mandelic acid Complexes in Aqueous Solutions. - Jraikuos, Hasan (Latakia University Journal -Basic Sciences Series, 2019)
In the present work, the photochemical reduction of Cr(VI) induced by iron(III)-mandelate complexes in aqeuous solutions was studied. Comparison experiments of Cr(VI) photoreduction in -system were carried out for determining the optimal experimental conditions. The effects of and initial concentrations of various reactants [Fe(III), mandelate and Cr(VI)] on the photoreduction efficiency of Cr(VI) were investigated. Experimental results indicate that the photoreactive iron(III)-mandelate complex is able to reduce Cr(VI) under UV/VIS light , and the optimum value for photochemical reduction of Cr(VI) is a bout . The chromium(VI) photoreduction efficiency increases with increasing initial concentrations of Fe(III) or mandelate, but it decreases with increasing initial concentrations of Cr(VI). In addition, the probable mechanism of the photochemical reduction of Cr(VI) by photoreactive iron(III)-mandelate complex in aqeuous solution has been suggested.